Maternal deprivation alters expression of neural maturation gene tbr1 in the amygdala paralaminar nucleus in infant female macaques. Issue 2 (4th December 2016) - de Campo, Danielle M.; Cameron, Judy L.; Miano, Joseph M.; Lewis, David A.; Mirnics, Karoly; Fudge, Julie L.
Abstract: Early parental loss is associated with social–emotional dysregulation and amygdala physiologic changes. Previously, we examined whole amygdala gene expression in infant monkeys exposed to early maternal deprivation. Here, we focus on an amygdala region with immature neurons at birth: the paralaminar nucleus (PL). We hypothesized that 1) the normal infant PL is enriched in a subset of neural maturation (NM) genes compared to a nearby amygdala subregion; and 2) maternal deprivation would downregulate expression of NM transcripts (mRNA). mRNAs for bcl2, doublecortin, neuroD1, and tbr1 —genes expressed in post‐mitotic neurons—were enriched in the normal PL. Maternal deprivation at either 1 week or 1 month of age resulted in PL‐specific downregulation of tbr1 —a transcription factor necessary for directing neuroblasts to a glutamatergic phenotype. tbr1 expression also correlated with typical social behaviors. We conclude that maternal deprivation influences glutamatergic neuronal development in the PL, possibly influencing circuits mediating social learning.